Selfie as a Communication Media of the 21st Century - Saavedra Vásquez, Valeria (2017)
The Selfie phenomenon is a social activity related to technology, it analyzes this phenomenon according to postulates and conceptual categories of David Morley like domestication and mediation of technological devices. It describes the rise of the Selfie phenomenon as consequence of modernity and technological progress in modern and traditional societies. It details the different reason for sharing a Selfie and what it intends to communicate.